Reaktivität und Selektivität in der Chemie der Diolefin-Metallkomplexe - Albrecht Salzer (CHIMIA)
The general reactivity of diolefin tricarbonyliron complexes is discussed with regard to their utility in organic synthesis. They are readily convertible into cationic allyl and dienyl complexes, which react regio- and stereospecifically with a large variety of nucleophiles. Special emphasis is put on the reaction with tertiary phosphines and phosphites, where new routes to β,γ-unsaturated phosphonium salts and phosphonates are opened. The reactivity of novel metal-coordinated ylids is also described. Functionalised diolefins like hexadien(2,4)al are stabilised against undesirable side reactions by metal complexation. Some of the products are useful for enantioselective natural product synthesis. In some cases, the condensation is accompanied by un unprecedented base-induced metal migration.